Evaluating the Efficacy and Safety of Cymbopogon Schoenanthus Syrup for Asthma and Allergies: A Two-Decade Clinical Study (American Journal of Multidisciplinary Research and Innovation, 2024)
Asthma and allergies are prevalent respiratory conditions affecting millions worldwide, often necessitating long-term management and treatment. Synthetic medications, while effective, may pose risks and adverse effects, prompting exploration into natural alternatives. This study investigates the efficacy and safety of a botanical syrup supplement derived from Cymbopogon Schoenanthus subsp. proximus, known as “Binj” or “Abba” in the United Arab Emirates (UAE), for the management of asthma and allergies. Through collaborative efforts with reputable laboratories and universities, the botanical syrup’s therapeutic potential was rigorously evaluated, encompassing phytochemical analysis, biological testing, and extensive clinical trials spanning two decades. Results demonstrate notable improvements in lung function and skin health among patients with asthma and allergies, evidenced by enhanced vital capacity, forced vital capacity, and visible reduction in skin allergy symptoms. Furthermore, safety assessments indicate a favorable profile, with minimal adverse events reported. The recognition of the botanical syrup by the UAE Ministry of Health and international pharmaceutical companies underscores its significance and potential for widespread application. This discovery represents a promising advancement in natural medicine, offering a safe and effective alternative for individuals seeking holistic respiratory wellness. Future research should focus on large-scale clinical trials and long-term safety studies to further elucidate its therapeutic benefits and optimize clinical outcomes.